KARAKTERISTIK KLINIS PASIEN KEJANG DEMAM YANG DIRAWAT DI RUMAH SAKIT BAPTIS BATU - Yurika Elizabeth Susanti; Teguh Wahyudi (Bahasa Indonesia, 2020)
Introduction: Febrile seizure is the most common type of seizure in children, mostly occurred in children aged 6 months to 5 years. The aim of the study was to describe the demographic and clinical characteristics of febrile seizures in children in the Baptist Hospital Batu. Methods: This was a cross-sectional research, including febrile seizure children (n=41) who were admitted into the Baptist Hospital Batu on January 2017 to October 2018. The data was collected from the medical records and described and presented in frequency tables. Results: Febrile seizure was common in boys (61%), aged 1 to 2 years old (46.3%). Generalized seizure (97.6%) was the most febrile seizures. The duration of seizure was <15 minutes (95.1%) with the majority patients with febrile seizure experience one seizure episode (73.2%). Simple febrile seizure (70.7%) was more common than complex febrile seizures. The body temperature was ≥38⁰ C (68.3%), however, the leukocyte counts was normal (63.4%). Conclusion: Febrile children younger than 2 years old, especially boys need to be well monitored as these children may develop into febrile seizure.